2018
DOI: 10.1038/s41377-018-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

Spin-controlled wavefront shaping with plasmonic chiral geometric metasurfaces

Abstract: Metasurfaces, as a two-dimensional (2D) version of metamaterials, have drawn considerable attention for their revolutionary capability in manipulating the amplitude, phase, and polarization of light. As one of the most important types of metasurfaces, geometric metasurfaces provide a versatile platform for controlling optical phase distributions due to the geometric nature of the generated phase profile. However, it remains a great challenge to design geometric metasurfaces for realizing spin-switchable functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(111 citation statements)
references
References 47 publications
(47 reference statements)
2
96
0
Order By: Relevance
“…In contrast, the majority of the experimental demonstrations of chiroptical effects in visible and near infrared range have reported circular dichroism in transmission. 8,[14][15][16][17][18][20][21][22]29,46 Among these, the most notable ones include a demonstration of a chiral metasurface by Zhu et al 8 , which achieved spin filtering with an extinction ratio of ∼ 9 : 1 while almost ∼ 90% of light with the selected helicity was transmitted, and a planarized chiral structure made of multiple layers of twisted metamaterials by Zhao et al 16 . The latter structure exhibits almost ∼ 30% transmission difference (and the extinction ratio of Our PC mirror outperforms most of the chiral mirrors realized to date in most categories, although its operational mechanism introduces some sensitivity to the angle of incidence and its resonant nature gives rise to a relatively narrow operation band and a certain susceptibility to fabrication imperfections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the majority of the experimental demonstrations of chiroptical effects in visible and near infrared range have reported circular dichroism in transmission. 8,[14][15][16][17][18][20][21][22]29,46 Among these, the most notable ones include a demonstration of a chiral metasurface by Zhu et al 8 , which achieved spin filtering with an extinction ratio of ∼ 9 : 1 while almost ∼ 90% of light with the selected helicity was transmitted, and a planarized chiral structure made of multiple layers of twisted metamaterials by Zhao et al 16 . The latter structure exhibits almost ∼ 30% transmission difference (and the extinction ratio of Our PC mirror outperforms most of the chiral mirrors realized to date in most categories, although its operational mechanism introduces some sensitivity to the angle of incidence and its resonant nature gives rise to a relatively narrow operation band and a certain susceptibility to fabrication imperfections.…”
Section: Discussionmentioning
confidence: 99%
“…For this to occur, according to a long-held notion, the structure has to be composed of complicated three-dimensional chiral elements, such as helices or, alternatively, made of multi-layer patterns carrying structural chirality. 1,7 To date, several demonstrations of plasmon-assisted intrinsic chiroptical responses in metastructures composed of subwavelength array of 3D chiral shapes 7,[13][14][15] or multilayer patterns of mirrorsymmetry-broken structures [16][17][18][19][20][21] have been reported. Although such structures may exhibit strong and wide-band chiaroptical response, their fabrication is not compatible with 2D patterning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Optical metasurfaces, 2D counterparts of metamaterials, have provided unprecedented capabilities in the modification of light wavefront, enabling a plethora of novel applications such as generalized Snell's law of refraction, light beam shaping, Spin‐Hall effects, holograms, polarization control and analysis, and nonlinear dynamics . In comparison with traditional bulk lenses that rely on the required gradual phase change accomplished by controlling surface profile of the optical material, metalenses are ultrathin and ultraflat, which is desirable for device miniaturization and system integration.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at the cost of increased complexity in fabrication, a curved CPSS has been demonstrated in [26] where the CPSS is physically shaped to obtain the necessary reflection phase shifts from the wave propagation. On the other hand, planar phase-gradient chiral metasurfaces have also been demonstrated that take advantage of the geometrical phase shift [27][28][29][30]. In particular, these phase-gradient chiral metasurfaces realize spin-selective phase modulations by rotating individual chiral unit cells to acquire the Pancharatnam-Berry phase shifts along their surfaces [31].…”
Section: Introductionmentioning
confidence: 99%